1993
DOI: 10.1891/0047-2220.24.4.36
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Importance in Rehabilitation Counseling

Abstract: The perceived importance of knowledge areas underlying rehabilitation counselor credentialing was examined. A common core of knowledge with differences across respondent characteristics was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 0 publications
7
42
1
Order By: Relevance
“…The results of this study differ somewhat from the 10 knowledge domains described in the last major national study in this area (Leahy et al, 1993), which CRCC currently uses to guide the test specifications for the certification examination. Some of these differences are related to the methods employed in each of these studies.…”
Section: Relationship With Previous Researchcontrasting
confidence: 94%
See 1 more Smart Citation
“…The results of this study differ somewhat from the 10 knowledge domains described in the last major national study in this area (Leahy et al, 1993), which CRCC currently uses to guide the test specifications for the certification examination. Some of these differences are related to the methods employed in each of these studies.…”
Section: Relationship With Previous Researchcontrasting
confidence: 94%
“…This has resulted in a more detailed description of the functions and knowledge areas associated with the rehabilitation counselor's role. For example, the KVI, which was developed and used in the last formal study of CRCs (Leahy et al, 1993), consisted of 58 items (knowledge areas), compared to the 96 items on the KVI-R, which was used in the present study. Although the majority of the new knowledge items performed well and were rated by CRCs as clearly important to effective practice (e.g., substance abuse and treatment, social security programs, benefits and disincentives, techniques for individuals with psychological disabilities, transferable skills analysis, ethical decision making models and processes, clinical problem solving and critical thinking skills, negotiation and conflict resolution strategies, mental heath and psychiatric disability concepts), other knowledge areas were perceived by the respondents as only marginally important to practice (e.g., life care planning, techniques for evaluating earnings capacity and loss, business/ corporate terminology, human sexuality and disability issues, theories and techniques of clinical supervision).…”
Section: Emerging Knowledge Domains and Job Functionsmentioning
confidence: 99%
“…The KVI-R, third revision (Leahy et al, 2011;Leahy et al, 2003;Leahy, 1993) was used by Leahy et al (2011) to obtain data regarding CRCs' attitudes on their knowledge and preparedness across various competencies. The original validation of the instrument (Leahy, 1993) posits that it was developed to "empirically [derive] knowledge domains in the practice of rehabilitation counseling [and to identify] the similarities of knowledge importance across various counselor dimensions" (p. 130).…”
Section: Instrumentationmentioning
confidence: 99%
“…The original validation of the instrument (Leahy, 1993) posits that it was developed to "empirically [derive] knowledge domains in the practice of rehabilitation counseling [and to identify] the similarities of knowledge importance across various counselor dimensions" (p. 130). It is further described as assessing the importance of knowledge areas to respondents in their role as rehabilitation counselors in the settings in which the work and the degree of preparedness they feel they have in this area or standard as a result of their education and training.…”
Section: Instrumentationmentioning
confidence: 99%
“…A number of studies have identified the core job functions of a rehabilitation counselor (Emener & Rubin, 1980;Leahy, Chan, & Saunders, 2003;Leahy, Szymanski, & Linkowski, 1993;Muthard & Salomone, 1969;Rubin et al, 1984;. Some of these studies focused on the perceptions of rehabilitation counselors vis-à-vis what they considered important and relevant (Leahy et al, 2003;Mullins & Roessler, 1998), whereas others examined the extent to which a job function or task was utilized in the rehabilitation counselors day-to-day practice (Emener & Rubin, 1980;Hayward & Schimdt-Davis, 2005).…”
mentioning
confidence: 99%